Network Ties Among Low-Tax Firms - Brown, Jennifer L.; Drake, Katharine D. (The Accounting Review, 2014)
ABSTRACT This study examines (1) whether network ties help explain variation in tax avoidance, and (2) how the relation between network ties and tax avoidance varies depending on the nature and context of those ties. We posit that information on a range of tax-avoidance strategies is shared among firms through their social network connections. Using board interlocks to proxy for these connections, we find that firms with greater board ties to low-tax firms have lower cash ETRs themselves. Ties to low-tax firms are more influential when the focal firm and its network partner are operationally and strategically similar, as are ties created by executive directors. Board ties to low-tax firms are also more influential when the focal firm and its network partner engage the same local auditor. Overall, our results suggest that the influence of firms' network ties on their tax-avoidance behavior depends on the character of those ties.